2009
DOI: 10.1111/j.1468-1293.2009.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of and virological response to antiretroviral therapy among HIV‐infected former and current injecting drug users and persons in an opiate substitution treatment programme: the Swiss HIV Cohort Study

Abstract: ObjectivesThe aim of the study was to investigate the influence of continued injecting drug use, enrolment in an opiate substitution treatment programme (OSTP), or cessation of injecting drug use on the uptake and course of antiretroviral therapy (ART). DesignA prospective observational study of all participants in the Swiss HIV Cohort Study followed between 1997 and 2006 was carried out. MethodsWe distinguished four groups of former or current injecting drug users (IDUs): (i) abstinent former IDUs; (ii) perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
75
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 53 publications
9
75
0
Order By: Relevance
“…Older age may be a proxy for less mobility and more comorbidity. Although a large proportion of participants with IDU as the transmission risk in Switzerland have stopped injecting drugs [30], IDU remains an important and independent risk factor for LTFU [10,11,29]. People with a higher baseline CD4 cell count or who were treatment-naïve were more prone to LTFU, a finding in congruence with research from France [29].…”
Section: Discussionsupporting
confidence: 75%
“…Older age may be a proxy for less mobility and more comorbidity. Although a large proportion of participants with IDU as the transmission risk in Switzerland have stopped injecting drugs [30], IDU remains an important and independent risk factor for LTFU [10,11,29]. People with a higher baseline CD4 cell count or who were treatment-naïve were more prone to LTFU, a finding in congruence with research from France [29].…”
Section: Discussionsupporting
confidence: 75%
“…3 Opioid substitution therapy programmes are effective in substantially reducing illicit opiate use, HIV risk behaviours, death from overdose and criminal activity, and financial and other stresses on drug users and their families. [4][5][6] These programmes also improve adherence to antiretroviral therapy and the physical and mental health of injecting drug users. [4][5][6] Many injecting drug users who would otherwise have no contact with any health services are attracted by these programmes, which then act as gateways to other services including primary health care, HIV testing, antiretroviral therapy and services for tuberculosis, hepatitis C and sexually transmitted infections.…”
mentioning
confidence: 99%
“…[4][5][6] These programmes also improve adherence to antiretroviral therapy and the physical and mental health of injecting drug users. [4][5][6] Many injecting drug users who would otherwise have no contact with any health services are attracted by these programmes, which then act as gateways to other services including primary health care, HIV testing, antiretroviral therapy and services for tuberculosis, hepatitis C and sexually transmitted infections. 7 Additionally, a critical ingredient of the HIV-prevention response is mobilization of affected communities, which is only possible for injecting drug users when they are not fully occupied with obtaining an ongoing supply of illicit drugs.…”
mentioning
confidence: 99%
“…Care of IDUs (intravenous drug users) requires interdisciplinary treatment of drug addiction and its psychosocial and somatic complications [10]. There are different treatment modalities available in different countries and studies have shown that treatment interventions can have great benefits.…”
Section: Introductionmentioning
confidence: 99%